2004
DOI: 10.1007/s11095-004-7674-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical Delivery of Anti-sense Oligonucleotides Using Low-Frequency Sonophoresis

Abstract: These results show successful delivery of anti-sense oligonucleotides using low-frequency ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 21 publications
(16 reference statements)
2
52
0
2
Order By: Relevance
“…Focusing on the NPs-assisted ultrasound as the aim of this review, a first study supporting the delivery of oligonucleotides by the application of LFS (20 kHz, 2.4 W/cm 2 , 50% duty cycle, 10 min) across the fullthickness pig skin was reported by Tezel et al [39]. Similarly, Tran et al delivered small interfering RNA loaded into cationic liposomes to melanocytic tumors present in skin to retard melanoma development.…”
Section: Sonophoresismentioning
confidence: 98%
“…Focusing on the NPs-assisted ultrasound as the aim of this review, a first study supporting the delivery of oligonucleotides by the application of LFS (20 kHz, 2.4 W/cm 2 , 50% duty cycle, 10 min) across the fullthickness pig skin was reported by Tezel et al [39]. Similarly, Tran et al delivered small interfering RNA loaded into cationic liposomes to melanocytic tumors present in skin to retard melanoma development.…”
Section: Sonophoresismentioning
confidence: 98%
“…Sonophoresis has been used for a while in physical therapy clinics for the localized treatment of pain and other indications. Several research articles have also indicated the effectiveness of this technique to deliver peptides and proteins such as insulin (67)(68)(69)(70)(71), heparin (72), γ-interferon and erythropoietin (70) along with other hormones (73) and oligoneucleotides (74). However, the degree of enhancement in drug delivery is highly dependent on the physicochemical properties of the drug (75).…”
Section: Sonophoresis/phonophoresismentioning
confidence: 99%
“…Heterogeneous penetration led to the formation of localized transport pathways, which occupied about 5% of the total exposed skin area. Tezel et al, 2004.…”
Section: Oligonucleotidsmentioning
confidence: 99%